Bladder Cancer is Associated with Low Plasma 25-hydroxyvitamin D Concentrations in Tunisian Population. (17th February 2016) - Ben Fradj, Mohamed Kacem; Gargouri, Mohamed Mourad; Hammami, Mohamed Bassem; Ben Rhouma, Sami; Kallel, Amani; Jemaa, Riadh; Feki, Moncef; Nouira, Yassine; Kaabachi, Naziha
Abstract: Little evidence suggests an impact of vitamin D on bladder cancer risk in Caucasians. This study aimed to investigate association of plasma 25-hydroxyvitamin D (25-OHD) with urothelial bladder cancer (UBC) risk in Tunisians. A case-control study included 250 patients with UBC and 250 healthy controls. Plasma 25-OHD was assessed by a competitive chemiluminescence immunoassay. Vitamin D deficiency and insufficiency were defined as 25-OHD <30 nmol/L and 30 to 49.99 nmol/L, respectively. Logistic regression models adjusting for gender, age, smoking status, duration of smoking, occupational exposure, and season were applied. Vitamin D deficiency (50.4% vs. 34.8%; P < 0.001) and insufficiency (40.4% vs. 26.8%; P < 0.001) were more frequent in patients than controls. Multivariate analysis showed that UBC is associated with vitamin D deficiency [odd-ratio (95% confidence interval), 3.71 (1.76–7.80); P = 0.001] and vitamin D insufficiency [2.65 (1.40–5.01); P = 0.003]. Other predictors of UBC were female gender, tobacco use, smoking duration, and occupational exposure. Plasma 25-OHD concentrations are low in Tunisian patients with UBC. These findings support experimental and epidemiological evidence of protective role of vitamin D against UBC but could not ascertain causal relationship. Further prospective studies and clinical trials are warranted to check causality.